2014
DOI: 10.11648/j.jps.20140205.23
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Seed Rates on Yield Contributing Traits in Wheat Varieties

Abstract: Abstract:A series of field experiments were conducted to determine the influence of different seed rates (100, 125 and 150 kg ha -1 ) on yield contributing traits of promising wheat varieties viz. Sarsabz, Kiran-95 and TD-1. The maximum germination, spike length and grains spike -1 was observed under seed rate of 125 kg ha -1 . The maximum plant population was recorded under seed rate of 150 kg ha -1 in Kiran-95 and highest grain weight spike -1 was noted under seed rate of 100 kg ha -1 in TD-1 variety. While … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 8 publications
10
12
0
1
Order By: Relevance
“…It may be due to the genetic character of the variety and higher photosynthesis efficiency. The results consistent with the findings of Nizamani et al [8] and Suleiman et al [9], who observed plant height, differed significantly among the varieties.…”
Section: Plant Height (Cm)supporting
confidence: 92%
“…It may be due to the genetic character of the variety and higher photosynthesis efficiency. The results consistent with the findings of Nizamani et al [8] and Suleiman et al [9], who observed plant height, differed significantly among the varieties.…”
Section: Plant Height (Cm)supporting
confidence: 92%
“…These results indicated that wider row spacing increased 1000-grain weight due to vigorous and bold seeds. These results were similar with the findings of Mali and Choudhary (2012) and Nizamani et al, (2014), who observed that 1000 grain weight increased with increasing plant spacing. Among different varieties, maximum 1000-grain weight (43.5 g) was recorded in variety WH 711, which was significantly higher than PBW 550 (41.4 g) and DBW 17 (40.0).…”
Section: Growthsupporting
confidence: 92%
“…Effect of row spacing and varieties on yields and harvest index of wheat during 2011-12 and 2012-13 in narrow rows than wider rows (Mali and Choudhary, 2013 and Kalpana et al, 2014). Among the varieties, WH 711 recorded significantly higher straw yield (83.9 q/ha) than PBW 550 (78.9 q/ha), but statistically at par with DBW 17 (81.8 q/ha).The harvest index was not influenced significantly by different row spacing but significant difference in harvest index was recorded among the varieties(Table 2).Variety PBW 550 recorded significantly higher harvest index (40.1%) than DBW 17 (38.6%) and WH 711 (38.0%).Higher harvest index of PBW 550 might be due to higher grain yield and lower straw yield(Bakht et al, 2007 andNizamani et al, 2014).The study concludes that narrow row spacing (15 cm) produced significantly higher grain yield as compared to wider spaced crop. Row spacing of 15 cm recorded about 8.54 and 12.21%, 3.35 and 7.04%, 1.22 and 0.70% higher yield than 22.5, 20 and 17.5 cm row spacing during 2011-12…”
mentioning
confidence: 97%
“…Wheat (Triticum aestivum L.) is one of the most important cereal crops used as a food all over the world. It ranks first in the world's cereal production and is a staple food for approximately one third of the world's population [1]. The grain contains about 60-80% carbohydrates, 8-15% protein, 1.5-2% fat, 1.5-2% inorganic ions, and vitamins (B complex and E) in small amounts [2].…”
Section: Introductionmentioning
confidence: 99%